Clinical impact of preformed donor‐specific denatured class I HLA antibodies after kidney transplantation. (13th March 2015) - Visentin, Jonathan; Marroc, Mélanie; Guidicelli, Gwendaline; Bachelet, Thomas; Nong, Thoa; Moreau, Jean‐François; Lee, Jar‐How; Merville, Pierre; Couzi, Lionel; Taupin, Jean‐Luc
Abstract Class I single‐antigen flow beads (SAFB) carry native and denatured human leukocyte antigen (HLA) molecules. Using a cohort of 179 class I HLA‐sensitized kidney recipients, we described incidence and clinical relevance of preformed denatured HLA donor‐specific antibodies (DSA) using two different assays: an acid‐treated SAFB assay (anti‐dHLA DSA) and the iBeads assays (SAFB+/iBeads‐ DSA). Eighty‐five class I DSA were found in 67 patients (median mean fluorescence intensity [MFI] of 1729 [range 520–13 882]). Anti‐dHLA and SAFB+/iBeads‐ DSA represented 11% and 18% of class I DSA and were mainly low MFI DSA (500–1000 MFI). Concordance between these two assays was good (90%). None of the patients with only class I anti‐dHLA DSA or only SAFB+/iBeads‐ DSA developed acute clinical antibody‐mediated rejection in the first‐year post‐transplantation, and their five‐yr death‐censored graft survival was similar to that of patients without DSA. Moreover, all these patients displayed a negative current T‐cell flow cytometry cross‐match. Therefore, both anti‐dHLA DSA and SAFB+/iBeads‐ DSA appear irrelevant, which could explain the good outcome observed in some patients with preformed class I DSA.